Deformation and Stress Analysis of Angiography Hand Rest - bin Hidzir Pauzi, Nabill; Firdaus Bin Abas, Mohamad; Azlina binti Mohd Salleh, Noor; Azam bin Abdullah, Shahrul; Rizwal bin Ismail, Johan (International Journal of Engineering and Technology, 2018)
Angiography is a test to observe the arteries in the limb using x-ray and a special dye. For this research, the angiography will be focusing on arms and hands. The patient’s arms and hands need to be still, to ease the process. Therefore, a device is needed to assist in holding the arms of the patient. Many of the medical personnel facing similar problems during an angiogram. The most common is the patients won’t stop moving and flinching while the tube entering the blood vessels. This can cause serious injury which can be fatal. They require the design to hold the patient’s arm and limiting their movement. This research will focus on the development of a device to address the above mentioned issues. The main objective of the project is to build a prototype of hand rest that will be able to hold the patient’s hand. The design will be suitable for the different age and physical build of the patients. It will be developed by using computer-aided design software; Solidworks. The device needs to be easy to use and adjustable for different patient size. With new invention, the problem can be reduced and shortened the queue time. The design will be an improvement to all angiogram facilities throughout the nation.